1977
DOI: 10.1007/bf02533276
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the hydrogen belts of membranes: I. Diester, diether, and dialkyl phosphatidylcholines and polyoxyethylene glycerides in monolayers with cholesterol

Abstract: The hydrogen belts of membranes are defined as the regions consisting of hydrogen bond acceptors, i.e., the C=O groups of glycero- and sphingolipids, and hydrogen bond donors, i.e., cholesterol-OH, sphingolipid-OH, proteins, and water. Lipid-lipid hydrogen bonding in these belts has been suggested. The connection of such hypothetical bonding with the condensation effect, i.e., the apparent reduction of surface area occupied by phospholipids in mixed monolayers with cholesterol, has been tested with lipids poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…It has been proposed in the past that the sterol hydroxyl group would play an essential role in hydrogen bridge formation between sterol and phospholipid [30][31][32]. There is, however, no experimental support for a direct interaction between phospholipid and sterol.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed in the past that the sterol hydroxyl group would play an essential role in hydrogen bridge formation between sterol and phospholipid [30][31][32]. There is, however, no experimental support for a direct interaction between phospholipid and sterol.…”
Section: Discussionmentioning
confidence: 99%
“…Our results contrast with those , who calculated a reduction of about 5 kcal mol"1 in activation energy and -16 cal mol"1 deg"1 in activation entropy for glycerol and urea permeation into diether-PC bilayers upon incorporation of cholesterol. Although the condensation effect of cholesterol was observed in monolayers of PC analogues lacking the carbonyl group (Fong et al, 1977), it was speculated that hydrogen bonding between the phospholipid carbonyl oxygen atom and the hydrogen of the cholesterol hydroxyl group is important in bilayers (Tirri et al, 1977). Schwarz & Paltauf (1977) reported that the rates of diffusion of Na+, Cl", and glucose across vesicles prepared from a diether-PC were not affected by incorporation of cholesterol to 30 mol % and suggested that the carbonyl oxygens may be required for PC-cholesterol interaction; however, cholesterol reduced the freedom of motion of a fatty acid spin probe to a similar extent in liposomes formed from each PC (Schwarz & Paltauf, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The ester linkage was found necessary for the permeability decrease produced by cholesterol in one study (88) but not in another study (89). Although the ester linkage may not be required for the effect of cholesterol on lipids, intermolecular hydrogen bonding may nevertheless occur (55). It would not result in a hydrogen-bonding network, however, and might even have the effect of breaking up such a network since it could only form a binary complex with another lipid.…”
Section: Hydrogen Bonding Of Lipids To Cholesterolmentioning
confidence: 93%